Barriers and Strategies in Digital Transformation Adoption Among Small and Medium Enterprises (SMEs) - Indria Guntararayana; Djoko Surahmat; Monesta Cici Ijan; Meci Nilam Sari; Margo Saptowinarko Prasetyo (West Science Journal Economic and Entrepreneurship, 2026)
This study examines the barriers and strategies associated with digital transformation (DT) adoption among small and medium enterprises (SMEs). Despite the growing importance of digital technologies in enhancing competitiveness and resilience, many SMEs remain at early stages of digital maturity. Employing a mixed-methods approach, this research integrates quantitative data from 450 SMEs across developed, emerging, and transitional economies with qualitative insights from case studies and expert interviews. The findings reveal that internal barriers, particularly financial constraints and digital skill gaps, are the most significant impediments to DT adoption, followed by organizational inertia and external challenges such as regulatory complexity and infrastructure limitations. The results further demonstrate that targeted strategies, including government subsidies, upskilling programs, and public-private partnerships, significantly improve digital adoption levels and firm performance. Notably, SMEs that successfully implement DT strategies experience higher revenue growth and enhanced operational efficiency. By extending the Technology–Organization–Environment (TOE) framework and Diffusion of Innovations (DOI) theory, this study highlights the importance of integrated and context-specific interventions. The research offers practical and policy-relevant implications for SME stakeholders, emphasizing the need for coordinated efforts to bridge the digital divide and foster inclusive digital transformation.